2018
DOI: 10.1080/19420862.2018.1505398
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and analysis of scFv-IgG bispecific antibody size variants

Abstract: Bispecific antibodies are an emergent class of biologics that is of increasing interest for therapeutic applications. In one bispecific antibody format, single-chain variable fragments (scFv) are linked to or inserted in different locations of an intact immunoglobulin G (IgG) molecule to confer dual epitope binding. To improve biochemical stability, cysteine residues are often engineered on the heavy- and light-chain regions of the scFv to form an intrachain disulfide bond. Although this disulfide bond often i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 34 publications
(21 reference statements)
0
25
0
Order By: Relevance
“…BisAb‐A contains the scFv fragment fused to the N‐terminus of the IgG V H domain (Coloma & Morrison, 1997), while BisAb‐B includes the scFv fragment attached to the C‐terminus of the IgG CH 3 domain (Dimasi et al, 2009). The BisAb‐C format's scFv fragment is located between the IgG Fab and Fc regions, directly above the hinge (DiGiandomenico et al, 2014), while the BisAb‐D format includes the scFv fragment inserted in the middle of the IgG CH 3 domain (Cao et al, 2018). Both BisAb‐C and BisAb‐D used Gly/Ser peptide linkers at the N‐ and C‐termini of the scFv fragments to connect each end to the IgG sequence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…BisAb‐A contains the scFv fragment fused to the N‐terminus of the IgG V H domain (Coloma & Morrison, 1997), while BisAb‐B includes the scFv fragment attached to the C‐terminus of the IgG CH 3 domain (Dimasi et al, 2009). The BisAb‐C format's scFv fragment is located between the IgG Fab and Fc regions, directly above the hinge (DiGiandomenico et al, 2014), while the BisAb‐D format includes the scFv fragment inserted in the middle of the IgG CH 3 domain (Cao et al, 2018). Both BisAb‐C and BisAb‐D used Gly/Ser peptide linkers at the N‐ and C‐termini of the scFv fragments to connect each end to the IgG sequence.…”
Section: Resultsmentioning
confidence: 99%
“…While BisAbs have shown promising biological activity in early‐stage research programs, the additional scFv fragments have posed unexpected challenges to BisAb manufacturing. It was recently reported that the engineered scFv cysteines of a scFv‐fusion BisAb produced monomer size variants and stable dimers with reduced bioactivity as a result of DSB mispairing (Cao et al, 2018). Unlike BisAbs, monoclonal antibody (mAb) fragmentation and aggregate formation during manufacturing processes has been previously studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these novel formats rely on engineered disulfide bonds to maintain the correct structure for in vivo activity. While there are examples demonstrating reduced mAbs can have similar biological activity compared with non‐reduced controls, (Wang, Liu, Cai, Huang, & Flynn, 2015) this has not been the case for novel formats where partial reduction can result in disulfide bond mis‐pairing, stable aggregates, and reduced biological activity (Cao et al, 2018). These results indicate that the consequence of reduction for therapeutics with novel structures are likely even more severe than for standard mAbs.…”
Section: Discussionmentioning
confidence: 99%
“…To do this, CHO-RS cells were stably transfected with a plasmid encoding a proprietary bispecific antibody (MEDI-X) bearing the reversible GPI-membrane anchor. MEDI-X is a symmetrically bispecific antibody consisting of an IgG with an inserted scFv in the CH3 domain (Cao et al, 2018). This bispecific was selected in part as an extensive conventional screen had been recently conducted that resulted in the isolation of cell lines capable of 1 g/L yields.…”
Section: Clonal Enrichment Of Difficult-to-express Proteinsmentioning
confidence: 99%